Magill's survey of world literature - Kellman, Steven G. 1947-; Magill, Frank N. (Frank Northen) 1907-1997 (Salem Press, 2009)
Offers profiles of major writers outside the United States from all time periods, accompanied by analysis of their significant titles of fiction, drama, poetry, and nonfiction.